Churronut: The feasibility study of establishing a food service enterprise in Pamantasan ng Lungsod ng Maynila - Fheevee D. Advincula, Aira Marie Bayani, Jewel Rose L. David., James A. Jacalne, Justin Mae D. Jazareno, Maria Theressa J. Legaspi, Shierlyn C. Marifosque, Bic P. Pineda, Carlo D. Puato, Mykhaella D. Rodriguez 4 0 16; 5
u
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila. 2023
Keywords: 2 -- 0; 6; 20; 20; 2